The role of arrows in the civilization of Mesopotamia - Aligaly, Rajaa Kadhim Ageel (Al-Adab Journal, 2022)
Arrows are one of the weapons of battles in the civilization of Mesopotamia, and they played a major role in achieving victories in wars. The cuneiform texts provided us with valuable, varied and important information about arrows and their names and designations related to them and their nature, as well as other aspects related to arrows, which are not related to the military dimension but to religious dimensions. And the association of arrows with the thought and belief of the inhabitants of Mesopotamia through their association with the gods, temples, rituals and other things. Also, arrows are linked to the societal dimension, as arrow makers formed a major role in providing the armed forces with the necessary equipment with arrows, as well as providing the people of the community with arrows that some needed in hunting and defending operations. The soul, especially with regard to commercial trips and its presence with the guards of commercial caravans, as the arrows had another dimension in the thought and belief of the inhabitants of Mesopotamia, especially with regard to their speed and the comparison of this speed with many vocabulary. They swear by the gods, their symbols, and the kings, as well as by tools and things of a religious nature that are related to the divine dimensions. Religious in the thought and belief of the inhabitants of Mesopotamia, as the concept of arrows was linked to the astronomical dimension and the vale dimension in the civilization of Mesopotamia, as well as to proverbs, wisdom, dreams and other many vocabulary of life, and in addition to all these axes there are texts supporting these axes, which we try in this research to shed light on their details minute.